Electrocatalytic Activity of Tungsten Carbide and Natural Zeolite Composite in Aqueous Solution - 程媛 谢伟淼 姚国新 胡素绢 李国华 (Chinese journal of chemical engineering, 2012)
Tungsten carbide and zeolite nanocomposite was prepared by combining a mechanochemical approach with a reduction and carbonization approach,using natural zeolite and ammonia metatungstate as precursors.The sample was characterized by X-ray diffraction and scanning electron microscope.The results showed that the crystal phase of the sample is composed of zeolite,monotungsten carbide and bitungsten carbide.The mass percentage and the crystallite diameter of tungsten carbide change along with the reacted time.Its electrocatalytic activity was measured with a microelectrode system with three electrodes.The results show that its electrocatalytic property is related to its crystal phase and the mass percentage of tungsten carbide,and its electrocatalytic activity is connected with the property of electrolyte,in which it is measured.Synergistic effect between tungsten carbide and zeolite is found during electrocatalysis.